Exploração de flores nativas do cerrado: o caso de Alto Paraíso - GO - Oliveira, Dagoberto Arraes G. de (2002)
This dissertation represents a reflection effort on the conservation and sustainable use of natural resources in this case, the native flowers of the Cerrado in altitude in an area located in the municipality of Alto Paraíso, Goiás State, Brazil; in the buffer zone of the National Park Chapada dos Veadeiros, inside the Cerrado Biosphere Reserve. Those flowers, of which there are 81 catalogued species in the study area, have a significant but poorly explored potential for using as food, medicine, decoration and raw material for handicraft. Their commercialization includes not only the local market, but also Brasília and other more distant urban centers like Curvelo and Diamantina, and foreign countries as well. The work consists of a characterization of the flowers exploitation system from extraction to commercialization and development of a methodological alternative of sustainable management, a Simplified Management Plan/Multiple Uses, on the basis of collective efforts. This requires community organization and a commitment to act in a less aggressive way towards the environment, in order to remove the obstacles which block a long term view of resources conservation. An experiment is proposed by applying this method to an area of 80 ha, under technical advisement of the Brazilian governmental agencies IBAMA and EMBRAPA.